Synergistic Valorisation of Fruit and Vegetable Waste for Bioenergy Production: A Review - Subbaiyan, Naveen; Perumal, Muthumari (International Research Journal of Multidisciplinary Technovation, 2024)
This review provides comprehensive information on the synergistic valorization of fruit and vegetable waste (FVW) for bioenergy production, addressing the urgent need for sustainable waste management and renewable energy sources. Due to their high organic content and substantial methane formation potential, FVW presents significant challenges. This review examines anaerobic digestion, composting, and thermochemical conversion processes, including pyrolysis and gasification. The emphasis is given to the combined use of these pathways, which allows maximizing the energy recovery and the resource utilization factor as well as reducing the environmental burden. The critical analysis of the main factors influencing the effectiveness of these processes is provided waste composition, process adjustments, and technical advancements. Recent studies indicated that pre-treatment methods improved conversion efficiency by up to 30%, and integrating multiple conversion pathways enhanced energy recovery by 20-40%. This comprehensive review concludes by discussing the prospects and challenges of commercial bioenergy production from FVW, integrating findings from recent scientific investigations and technological breakthroughs. The results of this work aim to enhance sustainable waste management strategies and contribute to a holistic circular bioeconomy vision.